Evidence for a second deflected prodelta of the Yellow River: Insights into a complex pattern of delta asymmetry. (September 2022) - Liu, Shihao; Feng, Aiping; Gao, Shu; Wang, Ya Ping; Jia, Jianjun; Du, Jun; Xu, Guoqiang; Li, Ping; Hu, Weifen; Feng, Wei
Abstract: The deflection of prodeltas caused by coastal currents is a significant contributor to deltaic asymmetry and clastic sediment masses on continental shelves. In the past, researchers supported that highly asymmetric deltas were usually unidirectional, or single-prodelta systems. Here, we present an exception in the Yellow River prodelta system. Using combined geophysical, lithological and geochemical evidence, the presence and pattern of Yellow River-derived subaqueous accumulation within the northwestern Bohai Sea were examined. We identified a northeastward alongshore transport mechanism that has resulted in arrays of shore-parallel, seabed trough-and-bump features predating the mid-Holocene highstand and a mudbelt capping most of these features since the highstand. The mudbelt is detached from the adjacent Luanhe River prodelta and thickens seaward and northeastward (downcurrent of the dominant coastal current). It includes a shoreface-detached mound that thickens to 10 m, and it overlaps and corresponds to the landward portion of the Bohai central muds. Geochemical evidence and previous provenance studies (using cores and surficial sediments collected from the central muds) have suggested that the majority of the central muds were supplied by the Yellow River and have accumulated since the mid-Holocene. We therefore interpret the central muds with a deflected prodelta of the Yellow Rive rather than the adjacent Luanhe River. This newly identified deflected prodelta, combined with the previously described "unique" Yellow River distal wedge off the Shandong Peninsula, resulted in a dual-prodelta system that consists of a pair of separated, highly asymmetric prodeltas. This system is a peculiar and complex pattern of deltaic asymmetry that has not been previously proposed. It is argued here that our case is dominated by regional bifurcated coastal currents and frequent lobe switching of the delta plain; a similar complex pattern of delta asymmetry can be expected under environments where plume deflections could undergo significant change. Highlights: An alongshore sediment-transport regime results in an additional deflected prodelta (Bohai central muds) of the Yellow River. The Yellow River Delta presents a peculiar pattern of deltaic asymmetry that includes a pair of highly asymmetric prodeltas. Bifurcation of coastal currents and frequent lobe switching contribute to formation of this peculiar asymmetrical pattern.